Environmental Management and Green Practices in the Construction Industry Across ASEAN Countries: A Comparative Study - Tie, Sing Yi; Emre, Mehmet; Bennani, Chafiq; Garcia, Sebastian; Talukdar, Gaurav; Maharjan, Rabin (Civil and Sustainable Urban Engineering, 2023)
The construction industry in Southeast Asian countries especially Association of Southeast Asian Nations receive substantial attention and investment for the high return value of the industry. This review aims to assess the environmental impact of the construction industry in ASEAN countries, analyzing current status, government policies, and innovative green materials and technologies to mitigate environmental effects and promote sustainability. It is important to note that construction industry is currently identified as one of the greatest waste production businesses which can cause adverse impacts and pollution to the environment that degrade the environmental quality. Construction and demolition wastes are emphasized and studied in the following context. The status and government policy on environmental management practices in ASEAN countries such as Malaysia, Vietnam and Singapore are reviewed and summarised in this article. Furthermore, green construction materials and green material technologies that are practised in ASEAN countries are examined throughout the study. The green materials include bamboo, recycled concrete aggregate, coconut husk and bagasse while the green material technologies include hydrogen energy, carbon capture and storage, and solar energy are discussed and evaluated with respective advantage and disadvantages.